2022
DOI: 10.1681/asn.2021050715
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Tertiary Lymphoid Tissues in Protocol Biopsies are Associated with Progressive Graft Dysfunction in Kidney Transplant Recipients

Abstract: Background: Tertiary lymphoid tissues (TLTs) are ectopic lymphoid tissues found in chronically inflamed organs. Although studies have documented TLT formation in transplanted kidneys, the clinical relevance of these TLTs remains controversial. We examined the impacts of TLTs on future graft function using our histological TLT maturity stages and the association between TLTs and Banff pathologic scores. We also analyzed the risk factors for the development of TLTs Methods: Serial protocol biopsy samples (0-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 73 publications
0
33
1
Order By: Relevance
“…The increased accumulation of plasmablast cells with high expression of immunoglobulins in the AK2 biopsy, 8 months after successful treatment of active AMR, may also contribute to the ongoing production of IgG antibodies directed against donor class I and class II HLA we noted in this patient after successful treatment of active AMR ( Table 1 ). None of our biopsies showed histological features of tertiary lymphoid tissues [ 73 ]. To our knowledge, the presence of functionally active long-lived plasma cells in successfully treated active AMR of kidney allograft have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The increased accumulation of plasmablast cells with high expression of immunoglobulins in the AK2 biopsy, 8 months after successful treatment of active AMR, may also contribute to the ongoing production of IgG antibodies directed against donor class I and class II HLA we noted in this patient after successful treatment of active AMR ( Table 1 ). None of our biopsies showed histological features of tertiary lymphoid tissues [ 73 ]. To our knowledge, the presence of functionally active long-lived plasma cells in successfully treated active AMR of kidney allograft have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between Tfh cells and B cells in renal cells can also organize structures that comprise functional germinal centers, defined as tertiary lymphoid organ (TLOs) (8,29,30). Past research has found TLOs in various CKD (31)(32)(33), and TLOs were observed in 37.5% of patients with IgAN (34). Interestingly, we found that Tfh cells co-localized with B cells on renal biopsy tissues of patients with IgAN, suggesting the existence of TLO in IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…TLS are mainly developed in non-lymphoid tissues to deal with various chronic inflammatory diseases including infection, autoimmune diseases, and cancer ( 49 ). However, they are not found in all patients, even those with the same disease ( 50 , 51 ).…”
Section: Background Of Tlsmentioning
confidence: 95%
“…TLS are mainly developed in non-lymphoid tissues to deal with various chronic inflammatory diseases including infection, autoimmune diseases, and cancer (49). However, they are not found in all patients, even those with the same disease (50,51). TLS in human solid tumors are essential for the creation of a favorable immune microenvironment to control tumor development.…”
Section: Functions Of Tlsmentioning
confidence: 99%